Efektivitas Modul Media Pemicu Program Sanitasi Total Berbasis Masyarakat (STBM) di Permukiman Tepian Sungai Siak - Novita Rany; Oktavia Dewi; Herniwanti (Jurnal Penelitian Pendidikan IPA, 2022)
The Community-Led Total Sanitation Program is an approach to change sanitation hygiene behavior through triggering activities, which has not yet achieved the national target. This study aimed to analyze the implementation of the Community-Led Total Sanitation Program in a sustainable environment in a suburban settlement. This was a qualitative study with an action research approach in three districts in the Siak River suburb. The participants of this study were residents who lived on the banks of the Siak river and the holders of the Environmental Health Program at the Public Health Center. Data were collected through direct observation and in-depth interviews regarding the Open Defecation Free (ODF) program, handwashing with soap, household food and beverage management, household waste management, and household liquid waste management. This study found that the community-led total sanitation program in the suburban of the three sub-districts of the city of Pekanbaru was not well implemented yet, especially in the ecological aspects of the Open Defecation Free (ODF) program, waste management, and liquid waste management program. Economically, the implementation of the program by non-governmental organizations had not been supported. Socially, health workers and community leaders provided education related to environmental sanitation and obtained a level of interpretation above 70%.